Quality of Japanese quail eggs according to different storage periods and temperatures - Carvalho, Débora Cristine de Oliveira; Nunes , Kilvia Ramila Barros; Gois, Glayciane Costa; Moraes , Elenice Andrade; Gonçalves-Gervásio, Rita de Cássia; Borges , Mônica Cristina Rezende Zuffo; Rodrigues, Rafael Torres de Souza; Brito , Claudson Oliveira (Acta Scientiarum. Animal Sciences, 2023)
The objective was to evaluate the quality of Japanese quail eggs stored at room temperature (26.8ºC) and under refrigeration (10.9ºC), for different storage periods (0; 5; 10; 15; 20; 25 and 30 days). A total of 196 quail eggs were assigned to different treatments in a factorial arrangement of 2 (temperatures) x 7 (storage periods), with 3 replications and 4 eggs per experimental unit. Data were subjected to regression analysis of parameters as a function of storage time at room temperature and under refrigeration. There was a reduction in egg weight, albumen weight and height, yolk height and egg yolk index with increasing storage period as a function of temperatures (p < 0.05). Eggs at room temperature showed a reduction in albumen index, while eggs under refrigeration showed a quadratic behavior (p < 0.05). Storage days promoted a quadratic response in albumen and yolk pH (p < 0.05) of eggs at room temperature. Eggs at room temperature floated from the 15th day of storage. When stored at room temperature, quail eggs show a sharp decrease in internal quality during storage for up to 30 days. Refrigerated storage is recommended.